Lyme Disease with Unknown Clinical Presentations: A Review of Seven Cases - Fatma SIRMATEL; Erdal POLAT; Şule Aydın TÜRKOĞLU (Mediterranean Journal of Infection, Microbes and Antimicrobials)
Introduction: Lyme disease (LD), caused by the bacterium Borrelia burgdorferi, is mostly caused by bites of infected ticks. LD can affect multiple body systems or organs, and produce a broad range of symptoms. It typically involves the skin, nervous system, musculoskeletal system and the heart. A history of confirmed exposure to tick bites, in the patients who had typical signs and symptoms of Lyme borreliosis and positive antibody tests for B. burgdorferi antibodies are basis of the diagnosis. The treatment of LD is determined mainly by the clinical manifestations of the disease. Antibiotics may cure most cases of LD. The early and quick therapy may provide complete recovery. In this paper, seven patients with LD who had different clinical pictures are presented. The aim of this review was to summarize current knowledge of the symptoms, clinical diagnosis and treatment of Lyme borreliosis. Materials and Methods: Seven patients with clinically and serologically confirmed LD who were admitted to our hospital in the past five years are presented. The patients clinically suggesting LD and whose serum specimens were positive for B. burgdorferi immunoglobulin G and immunoglobulin M antibodies by enzyme-linked immunosorbent assay (ELISA) were evaluated. Results: Four female and three male patients aged 19-64 years, were found to have LD with different clinical conditions. One patient had early localized LD (Erythema migrans), one had late disseminated LD, and five patients had early disseminated LD. The patients were treated with appropriate antibiotics. Conclusion: LD is a serious zoonotic disease mimicking all types of clinical presentation that may be diagnosed serologically. LD should be kept in mind in patients with a history of tick bite and presenting with different clinical findings. Appropriate antibiotic treatment should be initiated after serological investigations.